Performance Evaluation of Localization Algorithms for WSNs - C. Vargas-Rosales; J. Mass-Sanchez; E. Ruiz-Ibarra; D. Torres-Roman; A. Espinoza-Ruiz (International Journal of Distributed Sensor Networks)
In recent years, the use of wireless sensor networks has been increasing. Localization is a fundamental problem in wireless sensor networks (WSNs), since location information is essential for diverse applications such as tracking, quality network coverage, health, and energy efficiency. In this paper performance of localization algorithms such as range-free, range-based, and fuzzy-based decision is evaluated. We introduce a modification of an algorithm by providing weights to the correlation matrix to improve correctness. In all the cases the accuracy, precision, and computational complexity are evaluated as performance metrics. Location algorithms are evaluated using two scenarios, a first stage where all nodes are randomly distributed in a given area and a second scenario where four APs (access points) are placed on fixed positions and unknown nodes are randomly distributed within the sensing area. The received signal strength (RSS) is used to estimate the position of a node of interest. In the simulation results we show how our modified algorithm improves localization. On the other hand, we also have acceptable accuracy using distance-based algorithms, but they are more complex computationally.